PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI PADA MAHASISWA FEB UNIVERSITAS WIJAYA KUSUMA SURABAYA - Della, Meisya Fatma (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study is to identify the influence of financial literacy, financial behavior and income related to investment decisions made by students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The data used in this study includes primary data with 224 students as respondents. The methods used in this study include distributing questionnaires using the Link G-Form distribution method and direct distribution from class to class. Data analysis was carried out using SPSS 23 software. The findings of this study indicate a significant positive influence between financial literacy, financial behavior and income on investment decisions in FEB students, Wijaya Kusuma University, Surabaya.